2(4-3x)+3(x-2)=3 4(4+5x)-5(1-2x)= -1 3(2x+4)+2(1-x)=4 3(1-2x)+4(3x-1)=7 нужно до

nikitamerenkov nikitamerenkov    2   15.09.2019 09:20    1

Ответы
kotofrei231 kotofrei231  07.10.2020 16:44
2(4-3x)+3(x-2)=
38-6х+3х-6=38
3х-6х=38+6-38
-3х=6
х=6:(-3)
х=-2

4(4+5x)-5(1-2x)= -1
16+20х-5+10х=-1
20х+10х=-1-16+5
30х=10
х=10:30
х=1/3

3(2x+4)+2(1-x)=4
6x+8+2-2х=4
6х-2х=4-2-8
4х=-6
х=-6:4
х=-1.5

3(1-2x)+4(3x-1)=7
3-6х+12х-4=7
12х-6х=7+4-3
6х=8
х=8:6
х=1 1/3
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика